A Taxonomical Account Of Knowledge Creation In Organizations: Research Directions - Izunwanne, Pamela C. (Journal of Knowledge Management Practice, 2011)
The global knowledge economy could become the next booming economy. This point can be buttressed by the flood of literature on knowledge management. New job roles have emerged in many firms to handle the challenge of the global knowledge economy. But despite the developments, there are still gaps in literature and divergent views about the subject of knowledge and how it can be created. Knowledge is an abstract term that captures the art of knowing and what is being known, is difficult to study (Davenport and Völpel 2001). Knowledge management, the application of knowledge in organizations can be broken down into knowledge creation, knowledge sharing and knowledge transfer (Alavi and Leidner 2001, Alavi and Leidner 1999, Nonaka 1994b). These three elements are difficult to separate in practice(Argote et al. 2003), but this article focuses on presenting a taxonomical review of Knowledge creation in organizations, highlighting challenges involved, methods, approaches and directions for research.
Keywords: Knowledge creation; knowledge creation outcome; knowledge intensive organizations